Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content:1. The level of leadership skills among gifted students in the general education stage in the Qassim regionMrs. Noorah Yousef Aljuhany 2. The Reality of Applying Administrative Transparency in King Abdulaziz University from the Perspective of Department Heads and Female SupervisorsMrs. Asma Ali Hamdan Alshehri , Prof. Najat Mohammed Saeed Alsaigh 3. Difficulties learning reading skills for kindergarten students from the perspectives of kindergarten teachers, administrators, and supervisorsMrs. Worood Tayseer Sawalha , Dr. Ali Hassan Habayeb 4. The Degree to which Teachers of the First Three Grades Possess Effective Teaching Skills from the Point of View of Principals in Ain Al-Basha District in JordanMrs. Ruba Yasser Hyasat , Prof. Odeh Abdel-Gawad Abu Sneina 5. The Role of Artificial Intelligence Applications in Enhancing Educational Strategies in Higher Education (Literature Review)Dr. Wafa Fawaz Almalki 6. The Cognitive Load and its relation to Cognitive Holding Power among Umm Al- Qura University female studentsMrs. Atheer Khalid Al-Otaibi , Co-Prof. Nawar Muhammad Al-Harbi 7. A systematic review of studies of eye movement desensitization and reprocessing (EMDR) therapy for post-traumatic stress disorder from 2017 to 2021 documented in the Saudi digital libraryDr. Areej Salem Almehdar 8. Psychological burnout and its relationship to the quality of life of mothers of children with autism in the centers for people with special needs in KhartoumMrs. Sarah Mohamed Ahmed Alkashef
Keywords: Journal of Educational and Psychological Sciences